2020
DOI: 10.1016/j.jmh.2020.100026
|View full text |Cite
|
Sign up to set email alerts
|

Participation by conflict-affected and forcibly displaced communities in humanitarian healthcare responses: A systematic review

Abstract: Highlights The moderate quantity and quality of evidence indicate benefits from community participation. There was limited evidence on involvement of communities in framing problems or designing solutions. There was inadequate engagement with the construct of community participation and power relations. There was extremely weak evidence on participation by forcibly displaced communities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 34 publications
(184 reference statements)
1
25
0
2
Order By: Relevance
“…Emphasis should be placed on tailoring clinical interventions to the cultural and contextual particulars of specific refugee populations, such as resettled Syrian refugees ( 243 ). To support this, more should be done to increase community participation in both the design and implementation of health services for the forcibly displaced ( 244 ).…”
Section: Discussion and Recommendationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Emphasis should be placed on tailoring clinical interventions to the cultural and contextual particulars of specific refugee populations, such as resettled Syrian refugees ( 243 ). To support this, more should be done to increase community participation in both the design and implementation of health services for the forcibly displaced ( 244 ).…”
Section: Discussion and Recommendationsmentioning
confidence: 99%
“…To support this, more should be done to increase community participation in both the design and implementation of health services for the forcibly displaced (244).…”
Section: Capacity Building and Health Systems Strengtheningmentioning
confidence: 99%
“…Vertical programmes imposed on communities by external actors have a mixed history of success, and many studies identified low acceptability and poor feasibility in NPI maintenance over the medium- and long-term. An alternative model is increasingly being sought, with humanitarian actors working more closely with communities to implement sustainable programmes with viability over the long-term and complementing development programmes [115]. To support this view, the evidence suggested that many NPIs benefited from incorporating an RCCE component.…”
Section: Discussionmentioning
confidence: 99%
“…There is extensive literature on the role of community participation in humanitarian activities and evidence on the potential contribution of community engagement in crisis response and recovery (for reviews of this literature and evidence, see Brown et al, 2014;Rass et al, 2020;Bealt & Masouri, 2018). Evidence indicates that local participation can contribute to more effective information sharing where community groups have a more specific understanding of the affected setting (Bealt & Masouri, 2018, Brown et.…”
Section: Principles Of Participation In Humanitarian Responsementioning
confidence: 99%